Une formation interactive sur trois ans. La conservation préventive, un travail d’équipe - Marie-Dominique Parchas (In Situ)
Overview of training on preventive conservation in situ in archives and museum with the original setting up of working groups, their three years follow-up and evaluation of preventive conservation practices regularly updated.